Single Shot Coherence Properties of the Free-Electron Laser SACLA in the Hard X-ray Regime - Lehmkühler, Felix (Nature Publishing Group, 2014)
We measured the coherence properties of the free-electron laser SACLA on a single shot basis at an X-ray energy of 8 keV. By analysing small-angle X-ray scattering speckle patterns from colloidal dispersions we found a degree of transverse coherence of β(t) = 0.79 ± 0.09. Taking detector properties into account, we developed a simulation model in oder to determine the degree of coherence from intensity histograms. Finally we calculated a coherence time of τ(c) = 0.1 fs and a pulse duration of 5.2 fs which corresponds with previous predictions.